2007
DOI: 10.1088/0960-1317/17/12/016
|View full text |Cite
|
Sign up to set email alerts
|

A rhombic micromixer with asymmetrical flow for enhancing mixing

Abstract: A planar three-rhombus micromixer with two constriction elements for good mixing more than 84% at Re ⩾ 20 has been demonstrated by simulations and experiments. Higher constriction elements with low blockage ratios may enhance significant fluid mixing by combining principles of focusing/diverging, recirculation and Dean vortices. The local high flow velocity induced by the high constriction element provides both high inertial forces and centrifugal forces for enhancing mixing efficiency under asymmetrical flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…The performances of circular and rhombic SAR micromixers were compared numerically by Ansari and Kim [24]. A numerical and experimental study on an SAR-based rhombic micromixer was studied by Chung and Shih [25,26]. They compared the performances of rhombic micromixers with and without constriction at the recombine section.…”
Section: Open Accessmentioning
confidence: 99%
“…The performances of circular and rhombic SAR micromixers were compared numerically by Ansari and Kim [24]. A numerical and experimental study on an SAR-based rhombic micromixer was studied by Chung and Shih [25,26]. They compared the performances of rhombic micromixers with and without constriction at the recombine section.…”
Section: Open Accessmentioning
confidence: 99%
“…Regardless of which measure is used, it must be applied to compare the various devices developed and tested in different laboratories. The approach that has been frequently discussed and adopted (Yang et al 2005;Chung and Shih 2007;Chen and Yang 2008), accordingly, is considered to be an appropriate evaluation. The mixing performance of the micromixer was evaluated on calculating the mixing index of the droplet along the mixing channel at each time step.…”
Section: Quantitative Measure Of Mixingmentioning
confidence: 99%
“…One of the important design categories of the passive micromixer belongs to split and recombine of microchannels [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] where the main channel is split into two or more streams and then the sub-channels recombine after certain distance in a repetitive fashion. The split sub-channels can be three-dimensional or planar.…”
Section: Introductionmentioning
confidence: 99%
“…Planar split and recombine micromixers have been studied from simplest design with multiple streams [23][24][25][26][27][28]. Bessoth et al [23] reported a design of planar split and recombine micromixer with a total of 32 streams, which showed efficient mixing.…”
Section: Introductionmentioning
confidence: 99%